A narrativa de Maria Firmina dos Reis: nação e colonialidade - Laísa Marra de paula Cunha Bastos (2020)
This work aims to investigate the ways in which the narrative of Maria Firmina dos Reis (1822-1917) articulates nation and coloniality. Therefore, the main corpus of analysis is formed by Úrsula (1859), Gupeva (1861) and A escrava (1887). The hypothesis is that these texts approach hegemonic representations of the nation, and, at the same time, destabilize them by introducing perspectives of groups that were not conceived as national subjects, namely: indigenous people, Africans, black Brazilians and white Brazilian women. In this sense, two gestures developed by the author in her narratives are examined: the pedagogy for a new, anti-slavery, masculinity; and the positive representation of characters and speeches made inferior by the canonical nationalist imagination. In Gupeva, an Indianist short story of dark atmosphere, the plot shows contradictions without offering syntheses, since the contact between white men and indigenous people ends in dishonour and impossibility of future. In Ursula, these contradictions are combined around the antagonist, the metaphorically monstrous slave master, and are synthesized by his social, physical and moral disciplining, which is made through a combination of the nationalist and gothic repertoire. In the short story A Slave, openly abolitionist, the recognition of the memory of slavery and the victory of its black descendant suggest a somewhat more hopeful view of that late 19th century, as the final scene indicates, with the liberation of a young black man. It is argued that, when constructing interpretations of interethnic and gender relations based on colonialist violence, Firmina dos Reis moves away from literary images and projections around the whitening of the Brazilian national subject, which have codified reflections on Brazilianness, establishing a privileged place for the memory of injustices. As a result, the work of Maria Firmina dos Reis makes the field of 19th century Brazilian literature and the national imagination more embracing and complex.